2011
DOI: 10.1127/0003-5548/2011/0105
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and immune system: the size of the thymus as an indicator of the newborn's nutrition status

Abstract: The thymus is a central lymphatic organ reaching its largest size after the delivery. Its size is significantly affected by endogenous and exogenous negative factors. In our research, we investigated the relationship between the size of the thymus determined by sonography and anthropometric parameters as well as indexes demonstrating the nutritional status. The examined group consisted of 212 full-term newborns, all of which passed an anthropometric examination during the first five days after delivery (birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…Significant alterations in the structure of the thymus have been found, for example, in monkeys who experienced prenatal exposure to synthetic corticosteroids (Sawyer et al, 1977). In human samples, correlations have been found between the size of the thymus at birth and nutritional status (Collinson et al, 2003;Varg et al, 2011), as well as prenatal exposure to toxins such as arsenic (Raqib et al, 2009). Longerterm effects have been documented by McDade et al (2001): using data collected from a prospective longitudinal study of Fillipino children, they found a correlation between prenatal undernutrition and thymic function in adolescents that was marked by reduced thymopoietin production.…”
Section: 1mentioning
confidence: 96%
“…Significant alterations in the structure of the thymus have been found, for example, in monkeys who experienced prenatal exposure to synthetic corticosteroids (Sawyer et al, 1977). In human samples, correlations have been found between the size of the thymus at birth and nutritional status (Collinson et al, 2003;Varg et al, 2011), as well as prenatal exposure to toxins such as arsenic (Raqib et al, 2009). Longerterm effects have been documented by McDade et al (2001): using data collected from a prospective longitudinal study of Fillipino children, they found a correlation between prenatal undernutrition and thymic function in adolescents that was marked by reduced thymopoietin production.…”
Section: 1mentioning
confidence: 96%
“…Mechanistically, it is known that intrauterine growth restriction leads to disproportionate fetal growth and a high head to abdominal circumference ratio as a result of “brain sparing” responses, which direct nutrient-rich blood to maintain brain growth away from truncal organs including the thymus, with potential impact on immune development. Animal and human studies have linked fetal and birth anthropometric parameters indicative of undernutrition during pregnancy with smaller thymic size and impaired thymic development 12,33,34. We found that a larger fetal head circumference at 11 and 19 weeks’ gestation was linked with a higher risk of atopic eczema, with evidence of disproportionate head to abdominal circumference at 34 weeks.…”
Section: Discussionmentioning
confidence: 68%
“…Any such changes in premorbid growth may help explain the growth impairment in children with atopic eczema while also providing insights into etiology of the skin disorder. The development of inflammatory diseases such as atopic eczema is influenced by both genetic determinants and environmental exposures in early life, including poor nutrition,11,12 maternal stress,13,14 smoking,15 and microbiome-related exposures 16. With increasing evidence that atopic disease is partly determined by the fetal environment, better understanding of early life environment becomes crucial for identifying potential preventative strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The differences between prenatal and postnatal periods were evaluated by sonography method in intrauterine period. The studies evaluating thymus tissue in risky pregnancies in the last trimester are available in the literature [1][2][3][4][5][6]. Measurement of thymic size in the neonatal period may be useful in assessing the general immunological status of the child and response to sepsis in the neonatal period [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%